Reproductive medicine: still more ART than science? - Wilkinson, J; Bhattacharya, S; Duffy, J; Kamath, M; Marjoribanks, J; Repping, S; Vail, A; Van Wely, M; Farquhar, C (John Wiley & Sons, 2018)
The history of obstetrics and gynaecology is not a tale of evidence‐based practice. Tradition, expert opinion, and the lure of new technology have frequently superseded evidence as the primary driver for clinical decision making. The proof can be found in a litany of dubious interventions which have gained widespread popularity despite an absence of high quality data attesting to their effectiveness and, in some cases, ample credible evidence demonstrating harm. As a specialty, we have relied on investigations including X‐ray pelvimetry and antenatal stress tests, subjected innumerable women to stilboestrol and thalidomide, and have performed routine episiotomy in all primigravid women 1,. It is no surprise that, in 1979, Archie Cochrane famously awarded obstetrics the ‘wooden spoon’ for being the least evidence‐based specialty.